PELATIHAN SOFTWARE R UNTUK ANALISIS STATISTIK1 - Herlina Hanum (Lembaga Pengabdian pada Masyarakat, 2019)
R is a very useful software in statistical analysis. Its open-source nature makes it easy for users to download and use it freely. Its relatively small size allows R to be installed and used on a laptop because it doesn't use much laptop memory. Users are also facilitated to learn statistical analysis using R because there are many learning resources available which are also easily accessible. But the existence and ease of this has not been widely known by users of statistical analysis. To further introduce R to the public using statistical analysis, R training was conducted through the community service program (PPM) of Sriwijaya University. In this training, the introduction of R along with its potential use and development was carried out in statistical analysis. Participants were guided while practicing. The material studied included downloading and installing R, adding packages, calling data, naming and determining variable values, as well as some simple statistical analyzes. Statistical analysis studied descriptive, regression, and ANOVA. During training, participants can already download, install, and use R in accordance with the training material. For further use according to the needs of the participants, they are given some reference materials contained in a flash disk. In addition participants were also shown how to search for the required syntax via the internet.